Body composition changes in an endurance athlete using two different training strategies - Francis, P.; McCormack, W.; Caseley, A.; Copeman, J.; Jones, G. (The Journal of Sports Medicine and Physical Fitness, 2017)
Swimming, running and cycling are among the most popular and fastest growing sports in the world. Inherent in these sports is a desire to favorably alter body composition. Here we report a ~5.4 kg and ~5.3 kg fat tissue mass (FTM) loss in two separate interventions (12-16 weeks), in the same athlete, separated by 5 years. Whole body composition was assessed using dual X-ray absorptiometry (DXA). Dietary analysis for intervention 2 was completed using Mc Cance and Widdowson's composition of foods. In 2010, the male athlete (23 years, weight 85 kg, height 195 cm, 18.1% body fat) had a reduction of ~5.4 kg of FTM (15.4 vs. 10.0 kg) and an increase of ~5.1 kg of lean tissue mass (LTM) following 16 weeks of moderate intensity running (213±53 min/week) and circuit training (64±46 min/week). In 2015, the same athlete (28 years, 90.6 kg, 195 cm; 18.2%) had a ~5.3 kg loss of FTM and a ~0.8 kg increase in LTM after 12 weeks, predominately (75%) non-weight bearing exercise (49% cycling, 215±88 min/week; 25% running 110±47 min/week; 19% swimming, 83±27 min/week; 7% rowing machine, 29±26 min/week). Weekday and weekend dietary intake during intervention 2 were estimated as 2560 kcal and 3240 kcal per day, respectively. This report provides support for the hypothesis that an extended period of energy deficit is required to reduce body fat levels in amateur athletes independent of the mode of exercise